Sufficient Welfare Indicators Allowing Disagreement in Evaluations of Social Welfare - Kjell Arne Brekke; Hilde Lurås; Karine Nyborg (Statistics Norway, Research Department, 1994)
There is no consensus on how to measure interpersonally comparable, cardinal utility. Despite of this, people repeatedly make welfare evaluations in their everyday lives. However, people do not always agree on such evaluations, and this is one important reason for political disagreements. Thus, to keep in control of the normative premises, decision makers may prefer information which can be used as input in an arbitrary social welfare function to information which is the output from a social welfare function specified by the analyst. In this paper we try to identify sufficient welfare indicators; information which enable decision makers to arrive at welfare evaluations of social states or projects, according to their own ethical beliefs. Our conclusion is that providing factual information about different population groups; their social state, size, and characteristics, may be better for this purpose than the more traditional approach of focusing on ordinal utility information.
Keywords: A11; A13; D6; D7; I31; 330; Disagreement; interpersonal comparison; social welfare.